Evaluation of Supply Chain Practices followed by the Rice Industry Operating in India to Serve Market Demand - Viswanathan, Vignesh (2017)
Purpose: The following dissertation is aimed at investigating the current supply chain management practices adopted in the Indian rice industry and evaluating their effectiveness in meeting the market demands. Such understanding is critical in identifying the areas of improvement and enhancing the efficiency of the current practices. The presented research study aims at such identification, proposing recommendations for improvement and facilitating the growth and development of the Indian rice industry. Methodology: The research adopts a positivist research paradigm, with the study being guided by the deductive approach and exploratory research design. Both the primary and secondary data is used to address the research objectives, with the help of interviews and library research. Five supply chain managers in Indian rice industry, rice farmers in Tamilnadu and key retailers, are contacted to access the relevant information, which is analyzed using the thematic analysis tool to address the research questions and reach valid conclusions. Findings: The analysis and interpretation of the collected data indicate that the predominant supply chain management practices in the Indian rice industry are inspired by the traditional farming and supply chain practices, offering both advantages and disadvantages for the industry. Although the adoption of modern supply chain practices is evident, their effective integration and performance implications are lacking. The findings also suggest that the SCOR framework can be implemented, integrating the traditional and modern farming and supply chain management practices, to improve the performance efficiency of Indian rice supply network and effectively meet the market demands. Research Implications: The presented research has implications in both the academic and practical contexts. The research outcomes reveal the key strengths, limitations, and effectiveness of the Indian rice supply chain, addressing the literature gap identified. On the other hand, the retailers in the Indian rice industry would be able to use the research outcomes to improve the current supply chain management practices and adopt the suggested SOR framework to enhance the performance efficiency of the Indian rice supply network. Keywords: Supply Chain Management, Indian Rice Industry, SCOR Framework